Smokeless Tobacco: A Comprehensive Review of Molecular Effects, Societal Perception, and Cessation Strategies - Karishma Gangwani; Nandika Row; Shashi Anand; Srijan Acharya (BioMed)
Smokeless tobacco (ST) is an alternative to smoking, which involves not the burning of tobacco. Although ST has been used for thousands of years, its health effects are not well characterized, and it is the subject of misconceptions throughout society. Therefore, it is crucial to identify the risks associated with ST use. We conducted a comprehensive search of the scientific literature to identify studies reporting associations between tobacco chewing and the risk of oral cancer and premalignant lesions. Our review discusses the molecular mechanisms associated with ST components, along with the role of ST use in speech impairment and cancer progression. We also examine the effectiveness of tobacco cessation strategies and review the existing perceptions held by ST consumers. Our findings indicate significant health risks associated with ST use, including increased cancer risk and speech impairments. As societal perceptions and misconceptions about ST are important factors that influence its use, there is a need for comprehensive public awareness campaigns to correct these misconceptions and to promote healthier lifestyle choices. We call for further research to improve cessation interventions and to increase public awareness of relevant research discoveries. By providing a thorough discussion of the health impacts of ST, we aim to inform policy decisions and public health strategies to reduce the prevalence of ST use.